Application of Branding Through Product Photography To Develop Digital-Based MSMEs In Medokan Semampir, Surabaya - Dewi Candra Wulan; Budi Prabowo (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Many MSMEs do not understand the importance of branding, especially those involving social media. MSME actors should start taking advantage of ongoing technological developments for product branding. Lack of understanding about the importance of digital branding is also compounded by the lack of ability to produce quality, eye-catching product photos for digital branding purposes. In digital branding, product photos are very important to show brand identification and be able to attract consumers. Therefore, this community service activity was carried out with the intention of helping Medokan Semampir UMKM actors carry out digital branding activities through product photography. Community service is carried out through counseling, training, and assistance in making product photos. The results of the product photos are used for digital branding on social media. It seems that product photography is still not easily accepted because there are several MSME actors who are not familiar with the technology of the world of photography. In terms of taking product photos, MSME actors still need the help of the millennial generation to determine the proportionality of a photo. However, each MSME itself has been able to assess the use of the background and properties that are suitable for their products.